Multimodal nocturnal seizure detection in a residential care setting: A long-term prospective trial. (20th November 2018) - Arends, Johan; Thijs, Roland D.; Gutter, Thea; Ungureanu, Constantin; Cluitmans, Pierre; Van Dijk, Johannes; van Andel, Judith; Tan, Francis; de Weerd, Al; Vledder, Ben; Hofstra, Wytske; Lazeron, Richard; et al.
Abstract : Objective: To develop and prospectively evaluate a method of epileptic seizure detection combining heart rate and movement. Methods: In this multicenter, in-home, prospective, video-controlled cohort study, nocturnal seizures were detected by heart rate (photoplethysmography) or movement (3-D accelerometry) in persons with epilepsy and intellectual disability. Participants with >1 monthly major seizure wore a bracelet (Nightwatch) on the upper arm at night for 2 to 3 months. Major seizures were tonic-clonic, generalized tonic >30 seconds, hyperkinetic, or others, including clusters (>30 minutes) of short myoclonic/tonic seizures. The video of all events (alarms, nurse diaries) and 10% completely screened nights were reviewed to classify major (needing an alarm), minor (needing no alarm), or no seizure. Reliability was tested by interobserver agreement. We determined device performance, compared it to a bed sensor (Emfit), and evaluated the caregivers' user experience. Results: Twenty-eight of 34 admitted participants (1, 826 nights, 809 major seizures) completed the study. Interobserver agreement (major/no major seizures) was 0.77 (95% confidence interval [CI] 0.65–0.89). Median sensitivity per participant amounted to 86% (95% CI 77%–93%); the false-negative alarm rate was 0.03 per night (95% CI 0.01–0.05); and the positive predictive value was 49% (95% CI 33%–64%). The multimodal sensor showed a better sensitivity than the bed sensor (n = 14, median difference 58%, 95% CI 39%–80%, p < 0.001). The caregivers' questionnaire (n = 33) indicated good sensor acceptance and usability according to 28 and 27 participants, respectively. Conclusion: Combining heart rate and movement resulted in reliable detection of a broad range of nocturnal seizures.